IMPROVING STUDENTS’ READING COMPREHENSION USING LEARNING CELL TECHNIQUE - Gina Larasaty; Ayu Sulastri (Universitas Majalengka, 2019)
This research is talking about investigating whether learning cell technique can improve students’ reading comprehension in recount text. The research was conducted at SMK PGRI Indramayu. The population of this research were the students at X RPL grade of SMK PGRI Indramayu and the samples of this research consisted of 24 students. This research was conducted by using Classroom Action Research (CAR). The technique of collecting data used test and observation. This research was conducted only two cycles. The test included an objective 10 multiple choice, 5 true/false statements and 5 essay. The research finding showed that the data from two instruments, in preliminary test showed that the students reading comprehension was very low, the average in preliminary test was 50, 5. The result of students reading comprehension in cycle I was improved it was 66, 5. The result in cycle II showed improvement the student’s average score was 78. Based on the result of the research, it can be concluded that Learning Cell technique can improve the students ‘reading comprehension.